The Atypical Occurrence of Two Biotin Protein Ligases in Francisella novicida Is Due to Distinct Roles in Virulence and Biotin Metabolism - Youjun Feng (American Society for Microbiology, 2015)
ABSTRACT The physiological function of biotin requires biotin protein ligase activity in order to attach the coenzyme to its cognate proteins, which are enzymes involved in central metabolism. The model intracellular pathogen Francisella novicida is unusual in that it encodes two putative biotin protein ligases rather than the usual single enzyme. F. novicida BirA has a ligase domain as well as an N-terminal DNA-binding regulatory domain, similar to the prototypical BirA protein in E. coli. However, the second ligase, which we name BplA, lacks the N-terminal DNA binding motif. It has been unclear why a bacterium would encode these two disparate biotin protein ligases, since F. novicida contains only a single biotinylated protein. In vivo complementation and enzyme assays demonstrated that BirA and BplA are both functional biotin protein ligases, but BplA is a much more efficient enzyme. BirA, but not BplA, regulated transcription of the biotin synthetic operon. Expression of bplA (but not birA) increased significantly during F. novicida infection of macrophages. BplA (but not BirA) was required for bacterial replication within macrophages as well as in mice. These data demonstrate that F. novicida has evolved two distinct enzymes with specific roles; BplA possesses the major ligase activity, whereas BirA acts to regulate and thereby likely prevent wasteful synthesis of biotin. During infection BplA seems primarily employed to maximize the efficiency of biotin utilization without limiting the expression of biotin biosynthetic genes, representing a novel adaptation strategy that may also be used by other intracellular pathogens. IMPORTANCE Our findings show that Francisella novicida has evolved two functional biotin protein ligases, BplA and BirA. BplA is a much more efficient enzyme than BirA, and its expression is significantly induced upon infection of macrophages. Only BplA is required for F. novicida pathogenicity, whereas BirA prevents wasteful biotin synthesis. These data demonstrate that the atypical occurrence of two biotin protein ligases in F. novicida is linked to distinct roles in virulence and biotin metabolism.